Strategi Pemasaran UMKM Peternakan Ayam Petelur Kabupaten Tulungagung Dengan Pendekatan Analisis SWOT - Lapisna Dhiyah Yesikasari; Muhammad Aswad (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2022)
Marketing strategies are needed by the MSMEs of laying hens to win the competition in the target market. This study describes a marketing strategy that is suitable to be applied to MSME layer chicken farms in Tulungagung Regency by utilizing the SWOT analysis method (Strengths, Weaknesses, Opportunities, Threats). The results of this study indicate that the results of the IFAS matrix are 0.43 and the results of the EFAS matrix are 1.65. So that the SWOT diagram can occupy a quadrant 1 position, which means that the MSMEs of laying chicken farms in Tulungagung Regency are in a strong position and have many opportunities. According to the results of the SWOT matrix, the strategies that are suitable to be implemented are 1) strengthening capital to increase production capacity, 2) expanding laying hens farms in other places / regions, 3) maintaining the quality of the eggs produced, 4) adding and maintaining the existing distribution network. Yes, 5) increase skilled workforce, 6) maintain and improve good relations between breeders, communities and even financial institutions.